Kahoot!-Based Interactive Multimedia: Can it Increase Social Studies Learning Interest? - Sujarwo; Arita Marini; Yarmi, Gusti; Safitri, Sheila Syalma; Safitri, Desy; Dewiyani, Leola; Zahari, Musril (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The Industrial Revolution 4.0 requires teachers to adapt, master, and use technological devices supporting learning. However, the current problem is that many teachers still need help developing digital learning media for learning activities. This research aims to create interactive multimedia based on Kahoot! to increase fourth-grade elementary school student's interest in learning Social Sciences. This research uses the ADDIE model, which involves analysis, design, development, implementation, and evaluation. The research subjects were 30 elementary school students. This research uses a one-group pretest-posttest design. Data collection methods use questionnaires and tests. Data collection instruments use questionnaire sheets and test questions. Data analysis techniques use descriptive qualitative, quantitative analysis, and inferential statistics. The research results show a significant difference between the Pretest and post-test, which were treated using Kahoot! Multimedia based. Interactive multimedia based on Kahoot! can increase interest in learning Social Sciences in fourth-grade elementary school students.